Alarmins in Chronic Spontaneous Urticaria: Immunological Insights and Therapeutic Perspectives - Angela Rizzi; Federica Li Pomi; Riccardo Inchingolo; Marinella Viola; Francesco Borgia; Sebastiano Gangemi (Biomedicines)
Background: In the world, approximately 1% of the population suffers from chronic spontaneous urticaria (CSU), burdening patients’ quality of life and challenging clinicians in terms of treatment. Recent scientific evidence has unveiled the potential role of a family of molecules known as “alarmins” in the pathogenesis of CSU. Methods: Papers focusing on the potential pathogenetic role of alarmins in CSU with diagnostic (as biomarkers) and therapeutic implications, in English and published in PubMed, Scopus, Web of Science, as well as clinical studies registered in ClinicalTrials.gov and the EudraCT Public website, were reviewed. Results: The epithelial-derived alarmins thymic stromal lymphopoietin and IL-33 could be suitable diagnostic and prognostic biomarkers and possible therapeutic targets in CSU. The evidence on the role of non-epithelial-derived alarmins (heat shock proteins, S-100 proteins, eosinophil-derived neurotoxin, β-defensins, and acid uric to high-density lipoproteins ratio) is more heterogeneous and complex. Conclusions: More homogeneous studies on large cohorts, preferably supported by data from international registries, will be able to elucidate the intriguing and complex pathogenetic world of CSU.